Exploring the Relationship Between Job Satisfaction, Workplace Well-being, and Job Performance in an Office Facilities Solutions Service Provider - Gulane, Ian Rovii U.; Narsico, Peter G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examines the relationship between job satisfaction, workplace well-being, and job performance in the under-researched office facilities solutions sector. Unlike healthcare or manufacturing, this industry involves routine physical tasks, high client interaction, and varied contracts, yet lacks focused empirical study. Grounded in sustainable human resource management, the research explores how psychosocial workplace factors affect employee behavior and performance. Using a descriptive-correlational design, data were collected from 41 employees via Likert-scale surveys measuring five job satisfaction, three well-being, and six job performance indicators. Results showed all criteria were frequently observed, with mean scores above 3.80. A very strong positive correlation existed between job satisfaction and workplace well-being (r = .991, p < .01). Regression analysis confirmed both significantly predict job performance (R² = .983), supported by a significant ANOVA (F(2, 38) = 1084.44, p < .001). These findings offer novel sector-specific evidence highlighting the importance of role clarity, organizational support, and workplace conditions in boosting performance and morale. For HR managers and leaders, the study underscores the need to implement clear role communication, foster managerial respect, ensure job security, and promote supportive environments to enhance engagement and productivity. Embedding these factors into sustainable HR practices can reduce turnover, prevent burnout, and improve organizational outcomes. Limitations include self-reported data and a localized sample, suggesting future research should use longitudinal and multi-sector designs to strengthen generalizability.